Формування професійних компетентностей майбутніх офіцерів НГУ під час проведення комплексних польових занять - Кізян, Руслан Володимирович; Kizyan, Ruslan; Совінський, Сергій Євгенович; Sovinskyi, Serhii (Київський інститут Національної гвардії України, 2025)
У статті зазначено, що за результатами проведеного дослідження встановлено потреби основних груп стейкхолдерів у вдосконаленні практичних навичок здобувачів вищої військової освіти Національної гвардії України першого (бакалаврського) рівня. З’ясовано необхідність зосередження основної уваги на військово-професійній складовій освітнього процесу в сучасних умовах збройного протистояння російській агресії та спроможності здобувачів вищої військової освіти, як майбутніх офіцерів, ефективно керувати підлеглим особовим складом і успішно виконувати поставлені бойові завдання з урахуванням передового досвіду ведення бойових дій. Необхідною умовою цього є набуття здобувачами вищої освіти визначених професійними стандартами компетентностей. Зокрема, здатності планувати, організовувати і вести бій підрозділом, застосовувати тактичні прийоми спеціальних дій (операцій) військових формувань із правоохоронними функціями в різних умовах. Обґрунтовано теоретичні засади та запропоновано практичні рекомендації щодо вдосконалення умов формування означених компетентностей у освітньому процесі з використанням комплексних тактичних занять та двобічних тактичних навчань. Акцентовано увагу на вмінні майбутніх офіцерів грамотно планувати та ефективно керувати діями підлеглих.
Forming professional competences of future officers of the NGU during comprehemsive field training
The results of the study identified the needs of the main groups of stakeholders in improving the practical skills of applicants for higher military education of the National Guard of Ukraine at the first (bachelor’s) level, the need to focus on the military-professional component of the edu cational process in modern conditions of armed resistance to Russian aggression, as well as the ability of applicants for higher military education as future officers to effectively manage subordinate personnel and successfully carry out assigned combat missions, taking into account the best experience of conducting combat operations. In addition, it was found that a necessary condition for this is the acquisition by applicants for higher education of such competencies as the ability to plan, organize and conduct combat as a unit, to apply tactical techniques of special actions (operations) of military formations with law enforcement functions in various conditions. The article substantiates theoretical principles and develops practical recommendations for improving the conditions for the formation of these competencies in the educational process using complex tactical exercises and bilateral exercises during complex field exercises, focusing on the ability to competently plan and effectively manage the actions of subordinates by future officers. Further research may be aimed at diversifying the methods of conducting complex tactical training, combining it against the background of a single tactical situation with the use of weapons (conducting training shootings), including group weapons and the use of armored vehicles; adapting this lesson, based on the level of acquired knowledge and skills, for implementation with higher education students in the first, second and third years of study.
Keywords: професійна компетентність; здобувачі вищої освіти; майбутні офіцери; комплексне тактичне заняття; двобічне тактичне навчання; управління діями підрозділів у ході ведення бою; professional competence; higher education students; future officers; complex tactical training; bilateral tactical training; control of unit actions during combat